A simple interpretation of the effect of the polymer type on the properties of PMBs for road paving applications. (15th January 2018) - Saroufim, Edwina; Celauro, Clara; Mistretta, Maria Chiara
Highlights: Characterization of a PMB requires different tests to be carried out. This preliminary laboratory effort is costly and time consuming. Flow curves are proved to be useful in interpreting the influence of polymer type. This can be helpful in selecting promising polymer/bitumen blends for production. Abstract: The paper presents the results of the rheological characterisation of polymer-modified bitumen for paving applications. In order to find a simple interpretation of the influence of polymer type on the blends produced, in this study high density and low density polyethylene (PE) with different chemical properties were used, as well as ethylene-vinyl acetate. The chemical characteristics of the base bitumen and the polymers used were determined by means of SARA analysis and Fourier Transform Infrared Spectroscopy, FTIR, respectively. The morphology of the produced blends was investigated by means of fluorescent light optic microscopy, while the mechanical properties were investigated with both conventional tests and rheological measurements (dynamic mechanical analysis through frequency sweep test and viscosity measurements). The analysis of the modified bitumens was carried out based on the chemical structure and crystallinity properties of the polymer used. The flow curves (viscosity vs shear rate), in particular, proved to be an initial indicator of the type of modification attained. This shows that simple tests can be helpful in predicting the internal structure of the polymer modified binders (PMBs) and thus in selecting promising polymer/bitumen blends of the PE family to be submitted to full characterization for production purposes.